2019
DOI: 10.1186/s12870-019-1939-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of SlMAPK3 enhances tolerance to heat stress involving ROS homeostasis in tomato plants

Abstract: Background High temperature is a major environmental stress that limits plant growth and agriculture productivity. Mitogen-activated protein kinases (MAPKs) are highly conserved serine and threonine protein kinases that participate in response to diverse environmental stresses in plants. A total of 16 putative SlMAPK genes are identified in tomato, and SlMAPK3 is one of the most extensively studied SlMAPKs . However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 46 publications
(59 reference statements)
0
51
0
Order By: Relevance
“…It was observed that the relative expression of AtHSFA2 , AtHSFA6 , and AtHSFA7 was found to be higher in overexpression lines than the WT under both control as well as after HS conditions ( Figure 12 ). Apart from these, the expression of antioxidant enzymes were checked as ROS detoxification aids in HS adaptation and in possession of thermotolerance ( Yu et al, 2019 ). The expression of AtAPX2 was found to be upregulated in overexpression lines under HS conditions in comparison to the WT ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the relative expression of AtHSFA2 , AtHSFA6 , and AtHSFA7 was found to be higher in overexpression lines than the WT under both control as well as after HS conditions ( Figure 12 ). Apart from these, the expression of antioxidant enzymes were checked as ROS detoxification aids in HS adaptation and in possession of thermotolerance ( Yu et al, 2019 ). The expression of AtAPX2 was found to be upregulated in overexpression lines under HS conditions in comparison to the WT ( Figure 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most significant example given in a study was done on mitogen-activated protein kinase (MAPK) cascades. MAPK cascades are a part of signal transduction involved in plant development, hormone regulation, disease resistance, and stress responses [ 77 ]. Specifically, tomato MAK3 (SIMAPK3) has been known to defend against abiotic and biotic stresses.…”
Section: The Role Of Ros-scavenging Enzymes Under Thermal Stressmentioning
confidence: 99%
“…In short, ONAC127 and ONAC129, along with multiple pathways (sugar transportation), regulate caryopsis filling, including monosaccharide transporter OsMST6, sugar transporter OsSWEET4, calmodulin-like protein OsMSR2, AP2/ERF, OsEATB, cell wall construction, and nutrient transport under HS [66]. In tomato, CRISPRmediated Simapk3 mutant unveiled improved tolerance to HS, less cell damage and wilting, lower ROS contents, increasing antioxidant activity, and the higher expression of genes encoding heat shock factors/proteins (HSFs and HSPs) that mainly regulates HS [133]. In a different study, brassinazole resistant (BZR1) like protein available in tomato is involved in HS tolerance.…”
Section: The Contribution Of Gwasmentioning
confidence: 99%